Effects of maternal antibodies in infants on the immunogenicity and safety of inactivated polio vaccine in infants. Issue 5 (30th November 2022) - Gao, Shuyu; Wei, Mingwei; Chu, Kai; Li, Jingxin; Zhu, Fengcai
ABSTRACT: The presence of maternal poliovirus antibodies may interfere with the immune response to inactivated polio vaccine (IPV), and its influence on the safety of vaccination is not yet understood. A total of 1146 eligible infants were randomly assigned (1:1) to the IPV and Sabin IPV (SIPV) groups to compare and analyze the efficacy of the two vaccines in preventing poliovirus infection. We pooled the SIPV and IPV groups and reclassified them into the maternal poliovirus antibody-positive group (MAPG; ≥1: 8) and the maternal poliovirus antibody-negative group (MANG; <1: 8). We evaluated the impact of maternal poliovirus antibodies by comparing the geometric mean titer (GMT), seroconversion rate, and geometric mean increase (GMI) of types I–III poliovirus neutralizing antibodies post-vaccination, and incidence rates of adverse reactions following vaccination between the MAPG and MANG. Respective seroconversion rates in the MAPG and MANG were 94% and 100%, 79.27% and 100%, and 93.26% and 100% (all serotypes, P  < .01) for types I—III poliovirus, respectively. The GMT of all types of poliovirus antibodies in the MAPG (1319.13, 219.91, 764.11, respectively) were significantly lower than those in the MANG (1584.92, 286.73, 899.59, respectively) ( P  < .05). The GMI in the MAPG was significantly lower than that in the MANG ( P  < .05). No statistically significant difference in the incidence of local and systemic adverse reactions was observed between the MAPG and MANG. Thus, the presence of maternal poliovirus antibodies does not affect the safety of IPV but can negatively impact the immune responses in infants after IPV vaccination.